Psychological features of personal qualities impact on marketing specialists’ subject activity development - Mishchuk, Ivan (Personality and environmental issues, 2023)
The article examines the personal factors influencing the formation of subjective activity among marketing professionals. The theoretical principles of the subject and subjectivity concept in Ukrainian psychology are analyzed, along with their application in the labor market within business environments. Subjective activity is viewed as a complex systemic-integrative characteristic of an individual, indicating their ability for active, conscious transformation of oneself and the surrounding reality. It reflects the conscious self-realization of a person's inner natural essence, defining them as subjects of life activity and making them autonomous in their life manifestations. The research results on the influence of personal qualities and value structures of novice marketers and marketers with over two years of experience on the forms of their subjective activity are presented. Differences in the structure of relationships between indicators of subjective activity and the personal qualities and value structures of marketers with different levels of work experience are highlighted. It is emphasized that the formation of subjective activity is aimed at professional self-development and self-realization in the work process, serving as a crucial factor in professional growth and career advancement for specialists.